Design, synthesis, acetylcholinesterase inhibition and larvicidal activity of girgensohnine analogs on Aedes aegypti, vector of dengue fever (2014)
Girgensohnine alkaloid was used as a natural model in the design and generation of new alkaloid-like α-aminonitrilea series that was completed by the use of SSA-catalyzed Strecker reaction between commercial and inexpensive substituted benzaldehydes, piperidine (pyrrolidine, morpholine and N-methylpiperazine) and acetone cyanohydrin. Calculated ADMETox parameters of the designed analogs revealed their good pharmacokinetic profiles indicating lipophilic characteristics. In vitro AChE enzyme test showed that obtained a-aminonitriles could be considered as AChEIs with micromolar IC50 values ranging from 42.0 to 478.0 mM (10.3e124.0 mg/mL). Among this series, the best AChE inhibitor was the pyrrolidine a-aminonitrile 3 (IC50 ¼ 42 mM), followed by the piperidine a-aminonitriles 2 and 6 (IC50 ¼ 45 mM and IC50 ¼ 51 mM, respectively), and the compound 7 (IC50 ¼ 51 mM). In vivo insecticidal activity of more active AChEIs against Aedes aegypti larvae was also performed showing a good larvicidal activity at concentrations less than 140 ppm, highlighting products 2 and 7 that could serve as lead compounds to develop new potent and selective insecticides.